John Wesley: holiness of heart and life - Yrigoyen, Charles Jr.; Daugherty, Ruth A. (New York, N.Y : The Mission Education and Cultivation Program Department, 1996)
John Wesley: Holiness of Heart and Life is a six week study on John wesley, the major themes of his theology, the spread of Wesleyanism to North America, and renewal in the Wesleyan tradition.
Keywords: Wesley, John -- 1703-1791